Distinct accumulation patterns of soluble forms of E-selectin, VCAM-1 and ICAM-1 upon infusion of TNFα in tumor patients - Lieuw-a-Fa, Mariska; Schalkwijk, Casper; van Hinsbergh, Victor W.M. (Thrombosis and Haemostasis, 2003)
The transmigration of leukocytes across the endothelium is a prerequisite for the inflammatory process. Leukocyte-endothelium interaction is regulated by several endothelial adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and E-selectin. Their expression is enhanced by inflammatory mediators, such as TNFα. In vivo a small part of these adhesion molecules is shed by proteases, and can be detected in the circulation. In this study, the time course of the TNFα-induced accumulation in the blood of three circulating soluble adhesion molecules, sE-selectin, sICAM-1 and sVCAM-1, was studied in plasma samples of tumor patients enrolled in a phase I trial receiving TNFα. Two different cohorts were studied. Eleven patients received a continuous 24-hour TNFα infusion while 10 other patients received a 5-day continuous TNFα infusion. After 24 hours of TNFα infusion sE-selectin levels increased by 1985 ± 312 %, sVCAM-1 by 301± 19 % and sICAM-1 by 445 ± 82 %. Differences in accumulation patterns were observed after 5 days of continuous TNFα infusion. sVCAM-1 and sICAM-1 levels showed an increase during the infusion with a maximum at 3 to 5 days and stayed elevated after discontinuation of the TNFα infusion. In contrast, sE-selectin reached its peak at day 1 and declined thereafter. In conclusion, sVCAM-1 and sICAM-1 show a different accumulation pattern upon TNFα infusion as compared to sE-selectin in man.
Keywords: Leukocyte adhesion; cell adhesion molecule; endothelium; soluble receptor; inflammatory mediator; tumor necrosis factor